Researching Electronic Learning Contracts in Art and Design Masters Courses - Jefsioutine, Marie; Jerrard, Robert (Proceedings of the International Conference on Networked Learning, 2004)
This paper describes the conflation of specific areas of research involved in the development of an electronic (web-based) contract environment that aims to facilitate work-based learning in art and design masters courses. In particular, areas of research that have been developed over a number of years at Birmingham Institute of Art and Design through linking pedagogical review with the development and testing of technologies which ‘carry’ and network curricula. Within this project, research into aspects of work-based and distance learning, the contracted learning within masters courses in art and design, and the development, testing and evaluation of the student experience has been included.